Hot Spots and Blind Spots: Geographical Clusters of Firms and Innovation - Pouder, Richard W.; John, Caron H. St. (Academy of Management Review, 1996)
Hot spots are fast-growing geographic clusters of competing firms. Drawing on several literature streams, we develop an evolutionary model that contrasts hot spot and non-hot spot competitors within the same industry. Initially, economies of agglomeration, institutional forces, and managers' mental models create an innovative environment within the hot spot. Over time those same forces create a homogeneous macroculture that suppresses innovation, making hot spot competitors more susceptible than non-hot spot competitors to environmental jolts.